KRITIK SOSIAL-POLITIK DALAM QS. YUSUF AYAT 54-57 - Dara Humaira; Puji Astuti (MAGHZA, 2017)
This paper explains how the interpretation of Hamka and Sayyid Qutb is related to QS. Yusuf verses 54-57 and the social and political critique that characterized and became one of the characteristics of these two interpretations, since both are equally from literature, and also have similar experiences and similar societal conditions. Both of these commentaries, based on information from existing sources, are resolved by the interpreter while they are in prison. There are several important points concerning how both express and expose the political and social issues in the QS. Joseph 54-57, and also the differences that arise between these two interpretations. The point is that the title means that if it is accompanied by responsibility and trust, everything will be resolved while maintaining faith, patience, maintaining honor, and of course holding on to the provisions of God, and so on. While the difference that the author thinks is very striking in terms of delivery is that Sayyid Qutb can be regarded as someone who is anti with the oppressive government system, people who lick etc. Sentences are very clear and explicitly criticize the system of government. While Hamka conveyed her in a simpler form and tends to be implicit. Both make an interpretation as one of the media to preach and criticize the wrong understanding.